2019
DOI: 10.1093/mnras/stz212
|View full text |Cite
|
Sign up to set email alerts
|

TheThreeHundred Project: ram pressure and gas content of haloes and subhaloes in the phase-space plane

Abstract: We use TheThreeHundred project, a suite of 324 resimulated massive galaxy clusters embedded in a broad range of environments, to investigate (i) how the gas content of surrounding haloes correlates with phase-space position at z = 0, and (ii) to investigate the role that ram pressure plays in this correlation. By stacking all 324 normalised phase-space planes containing 169287 haloes and subhaloes, we show that the halo gas content is tightly correlated with phase-space position. At ∼ 1.5−2 R 200 of the cluste… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

12
76
4
6

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 72 publications
(98 citation statements)
references
References 69 publications
12
76
4
6
Order By: Relevance
“…In contrast to the higher cluster mass intervals, the low mass range also exhibits a star-forming, albeit small, population with positive radial velocity, especially at high redshift, indicating that quenching becomes more effective at lower redshift and higher cluster mass. This is in agreement with a suite of recent cluster resimulations by Arthur et al (2019), which find ram-pressure stripping of subhalos to be significantly enhanced in more massive halos compared to less massive halos.…”
Section: Mass and Temporal Evolutionsupporting
confidence: 91%
“…In contrast to the higher cluster mass intervals, the low mass range also exhibits a star-forming, albeit small, population with positive radial velocity, especially at high redshift, indicating that quenching becomes more effective at lower redshift and higher cluster mass. This is in agreement with a suite of recent cluster resimulations by Arthur et al (2019), which find ram-pressure stripping of subhalos to be significantly enhanced in more massive halos compared to less massive halos.…”
Section: Mass and Temporal Evolutionsupporting
confidence: 91%
“…Their main finding showed that radial gas fractions decrease with decreasing cluster-centric distance, and contamination from backsplash and pre-processed galaxies (which will also increase with decreasing cluster-centric distance) brings the distribution down. This is in disagreement with Lotz et al (2019) and Arthur et al (2019), who find that the instantaneous gas fraction does decline radially, but the gas in (sub)haloes is lost on first passage, rather than contamination being the cause for the radial decline. In fact, in Arthur et al (2019), it was postulated that the majority of gas in infalling objects is stripped by some sort of accretion shock at 1.5-2R 200 , where R 200 is the radius of the halo at 200 times the critical density of the universe at that redshift.…”
contrasting
confidence: 73%
“…This is in disagreement with Lotz et al (2019) and Arthur et al (2019), who find that the instantaneous gas fraction does decline radially, but the gas in (sub)haloes is lost on first passage, rather than contamination being the cause for the radial decline. In fact, in Arthur et al (2019), it was postulated that the majority of gas in infalling objects is stripped by some sort of accretion shock at 1.5-2R 200 , where R 200 is the radius of the halo at 200 times the critical density of the universe at that redshift. However, whilst galaxy star formation quenching has been well studied, a full examination of the gas in infalling objects is needed in order to possibly alleviate tension in the literature and learn more about pre-processing.…”
contrasting
confidence: 73%
“…Cosmological simulations show that ram pressure stripping is enhanced in cluster environments, and can lead to infalling galaxies being almost entirely stripped of their halo gas. This can occur even in the outskirts of a cluster, resulting in the quenching of star formation in cluster galaxies (Zinger et al 2018;Arthur et al 2019). Observational evidence for ram pressure stripping includes cluster galaxies whose molecular gas reservoirs have been disturbed, meaning the gas is distributed asymmetrically with respect to the stellar component of the galaxy (Zabel et al 2019).…”
Section: Introductionmentioning
confidence: 99%